Liability for Damage Caused by Domestic and Wild Animals in Turkish Law - Altunkaya, Mehmet; Guloglu, Yavuz; Belkayalı, Nur; Bulut, Alper; Cesur, İlknur (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract.The Turkish Code of Obligations holds pet owners objectively liable for any damage caused by their pets regardless of fault on the grounds that they failed to carry out their supervisory duty. There is, however, no regulation on compensation for damages caused by wild or stray animals. The legal gap in this field is filled by case laws. The aim of this study is to compare pet owner liability regulated by private law as strict liability and state liability for damage caused by wild animals protected by national legislation and international conventions. The research material consists of current legislation, and judicial and administrative decisions on property damage and bodily injury caused by animals. Tort claims for damages caused by pets and wild animals differ by statute of limitations, judicial remedy, the law on which the case is based, and strict liability principles. Pet owner liability for damage caused by the pet is based on strict liability in private law while administrative court decisions hold the administration liable based sometimes on strict liability and sometimes on negligence.Keywords: Pet owner liability; Pets; Wild animals; Strict liability; Compensation Abstrak.Kode Kewajiban Turki meminta pemilik hewan peliharaan bertanggung jawab secara obyektif atas kerusakan yang disebabkan oleh hewan peliharaan mereka, terlepas dari kesalahan yang dilakukan. Adapun alasan yang diajukan karena pemilik hewan gagal menjalankan tugas pengawasan. Namun, tidak ada peraturan tentang kompensasi atas kerusakan yang disebabkan oleh hewan liar atau tersesat tersebut. Tujuan dari penelitian ini adalah untuk membandingkan kewajiban pemilik hewan peliharaan yang diatur oleh hukum privat sebagai kewajiban yang ketat dan kewajiban negara atas kerusakan yang disebabkan oleh hewan liar yang dilindungi oleh undang-undang nasional dan konvensi internasional. Materi penelitian terdiri dari undang-undang saat ini, dan keputusan yudisial dan administratif tentang kerusakan properti dan cidera tubuh yang disebabkan oleh hewan. Klaim kerugian atas kerusakan yang disebabkan oleh hewan peliharaan dan hewan liar berbeda menurut undang-undang pembatasan, upaya hukum, hukum yang menjadi dasar kasus, dan prinsip tanggung jawab yang ketat. Tanggung jawab pemilik hewan peliharaan atas kerusakan yang disebabkan oleh hewan peliharaan didasarkan pada tanggung jawab yang ketat dalam hukum privat, sementara keputusan pengadilan administratif memegang tanggung jawab administrasi terkadang berdasarkan tanggung jawab yang ketat dan terkadang pada kelalaian.Kata kunci: Kewajiban pemilik hewan peliharaan; Hewan peliharaan; Hewan liar; Tanggung jawab yang ketat; Kompensasi Аннотация.Обязательственный кодекс Турции возлагает на владельцев домашних животных объективную ответственность за ущерб, причиненный их домашними животными, независимо от причиненного им вреда. Выдвинутые причины заключались в том, что владелец животного не выполнил свои обязанности по надзору за ним. Однако нет никаких правил относительно компенсации ущерба, причиненного дикими или бродячими животными. Целью этого исследования было сравнить обязанности владельцев домашних животных, регулируемые частным правом как строгое обязательство, и обязанности государства за ущерб, причиненный дикими животными, охраняемыми национальными законами и международными конвенциями. Материалы исследования состоят из действующего законодательства, судебных и административных решений в отношении имущественного ущерба и телесных повреждений, причиненных животными. Иски о возмещении ущерба, причиненного домашними и дикими животными, различаются в зависимости от закона об исковой давности, установленного закона, закона, на котором основано дело, и строгих принципов ответственности. Ответственность владельца домашнего животного за ущерб, причиненный домашним животным, основана на строгой ответственности по частному праву, в то время как решения административных судов предусматривают административную ответственность, иногда основанную на строгой ответственности, а иногда на небрежности.Ключевые слова: Обязанности владельцев домашних животных; Домашнее животное; Дикое животное; Строгая ответственность; Компенсация